IMPROVEMENT OF E-GOVERNANCE SYSTEM MANAGEMENT IN UZBEKISTAN - Radjabov Bunyod Abduhalilovich (Research Parks Publishers, 2020)
This article explores the theoretical and practical aspects of public procurement. The existing problems in the public procurement system of the Republic of Uzbekistan were identified and ways of ensuring their compliance with international requirements through studying the experience of foreign countries were presented. The article presents scientific proposals and practical recommendations on how to save budget funds allocated to the state budget and ensure their efficient and rational use.